Young people's expectations, preferences, and experiences of therapy: Effects on clinical outcome, service use, and help‐seeking intentions. (7th January 2014) - Watsford, Clare; Rickwood, Debra
Abstract Background Young people represent a vulnerable age group for mental health concerns and tend not to seek help. Exploring factors that influence young people's engagement in therapy and clinical outcomes is crucial. This study examined the relationships between young people's expectations, preferences, and actual experience of therapy on their clinical outcome, mental health care service use, and help‐seeking intentions. Gender and age effects were also explored. Methods A quantitative prospective research method was utilised. Participants included a total of 228 young people aged 12 to 25 years who completed an initial survey on contact with a youth mental health service and 102 who completed an online follow‐up survey 2 months later. Results Results showed that young people's actual experiences of therapy and their preference to be personally committed to therapy were positively associated with the outcome variables. No significant associations were evident for initial expectations. No age or gender effects was found. Conclusions These initial findings suggest that initial expectations may not be well formed for youth and appear not to be relevant to young people's engagement or outcomes, and are less important than motivation and actual experiences. Youth‐focused mental health services need to ensure a positive early experience to promote early intervention and relapse prevention.